Investigation of rs1746661 Polymorphism in FNDC5 Gene in Obese Patients - Elham Hadi; Hashem Nayeri; Ali Mohammad Ahadi; Ziba Rezvani Sichani (Disease and Diagnosis)
Background: Obesity is a multifactorial disorder that has considerably increased in developing countries in recent years. This disease results from an imbalance between energy intake and expenditure, influenced by various factors such as behavior, diet, environment, metabolic factors, and genetics. Different genetic aspects of obesity seek mutations in genes that are responsible for appetite control and metabolism. FNDC5 is a glycosylated membrane protein that is highly expressed in the heart, brain, and skeletal muscle tissues in mice. This protein is cleaved by an unknown protease at the cell surface. This study aimed to investigate the rs1746661 polymorphism in the FNDC5 gene among obese patients. Materials and Methods: The blood samples were collected from 100 individuals visiting Shariati Hospital in Isfahan and the Social Security Clinic for DNA extraction using the phenol-chloroform method, and informed consent was obtained from them for their participation in the study. Specific primers for G/A/T alleles were designed for the amplification refractory mutation system-polymerase chain reaction (PCR) method, and PCR was performed. The results were examined on agarose gel electrophoresis and statistically analyzed using SPSS 22 software. Results: Based on genetic analysis investigations, our findings revealed a significant association between the GT genotype in the rs1746661 polymorphism and the occurrence of obesity and/or other metabolic disorders. Such genotypes can be considered predisposing polymorphisms for obesity and/or other metabolic problems. Conclusion: Overall, the multifactorial nature of obesity, such as lifestyle and dietary habits, should receive special attention.